Analysis of mRNA populations by cDNA·mRNA hybrid-mediated inhibition of cell-free protein synthesis - Hastie, Nicholas D. (1978)
Hybridization of mRNA to its corresponding cDNA was found to specifically inhibit translation of the mRNA in vitro. Using hybridization of globin cDNA to globin mRNA as a model system, we found that equivalent amounts of cDNA were required both for the saturation of the mRNA hybridization and for complete inhibition of globin synthesis. Also, the rate of inactivation of translation was identical to the rate of hybridization and followed the predicted kinetic form. This assay has been applied to the analysis of a set of abundant mRNAs in mouse liver. Hybridization of liver mRNA with total liver cDNA in slight excess to a low C(0)t value specifically inhibited translation of several major polypeptides. Melting of the hybrids prior to translation restored synthesis of these polypeptides. Moreover, we found that different liver mRNAs are inactivated with different kinetics; the results suggest that the mRNAs for the major urinary polypeptide and for albumin are the most abundant and second most abundant, respectively, in mouse liver. The general applications of this technique are discussed.